Climate Change, International Migration, and Interstate Conflict - Cristina Cattaneo; Timothy Foreman (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
A number of factors contribute to interstate conflicts. One social element that has received little attention in the literature is the role of international migration. At the same time, the contribution of climate stress on interstate disputes has been underresearched. This paper analyses if climate stress represents a direct driver of interstate disputes and, at the same time, an indirect driver to conflicts through its effect on international migration. To do so, we use climate shocks to instrument for migration flows in a gravity setting in order to study its causal effect on international conflict. We find that a 1% increase in climate-induced migration increases the probability that the destination of the flows initiates conflict against the origin by 0.001 percentage points over a mean incidence of conflict of 0.13 percentage point per year. The results are consistent across different migration datasets and different specifications of defining the initiator in the conflict.
Keywords: 330